2004
DOI: 10.1056/nejmoa031145
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against Folate Receptors in Women with a Pregnancy Complicated by a Neural-Tube Defect

Abstract: Serum from women with a pregnancy complicated by a neural-tube defect contains autoantibodies that bind to folate receptors and can block the cellular uptake of folate. Further study is warranted to assess whether the observed association between maternal autoantibodies against folate receptors and neural-tube defects reflects a causal relation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
148
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(159 citation statements)
references
References 27 publications
3
148
0
6
Order By: Relevance
“…This suggested that if the AuAbs to the FR in women with NTD pregnancy are contributing to the fetal abnormalities, these could be rescued by folinic acid treatment. Subsequent analysis of human serum samples demonstrated the presence of FR α AuAbs in women with a history of an NTD pregnancy [ 8 ]. The properties of these antibodies were confirmed by the high-affinity binding to FR α ( K a = 10 9 -10 10 L/mol) and by their ability to block folate uptake in FR α -expressing KB cells in culture [ 8 ].…”
Section: Discovery Of Fr α Auabsmentioning
confidence: 96%
See 1 more Smart Citation
“…This suggested that if the AuAbs to the FR in women with NTD pregnancy are contributing to the fetal abnormalities, these could be rescued by folinic acid treatment. Subsequent analysis of human serum samples demonstrated the presence of FR α AuAbs in women with a history of an NTD pregnancy [ 8 ]. The properties of these antibodies were confirmed by the high-affinity binding to FR α ( K a = 10 9 -10 10 L/mol) and by their ability to block folate uptake in FR α -expressing KB cells in culture [ 8 ].…”
Section: Discovery Of Fr α Auabsmentioning
confidence: 96%
“…The benefits of folate supplementation in the absence of systemic folate deficiency or genetic abnormalities of folate pathways have not been adequately explained. The identification of FR autoantibodies (AuAbs) in women with a history of NTD pregnancy provides a mechanism by which the developing embryo could be deprived of folate [ 8 ]. Although the cause of this autoimmune disorder in mothers remains unknown, the AuAb directed against the FR α could disrupt folate transport to the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…187 This suggests that folate transfer to the fetus during pregnancy may be blocked, which may increase risk of neural tube defects. 188 Because these elevated autoantibodies were also present in at least one parent of children with autism, parental antibodies may contribute to autism etiology. 189 Two cohort studies and a case-control study found an association between maternal or family history of autoimmune diseases and ASD 124,190 or autistic regression, 191 whereas another case-control study found no association.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…Recently, Rothenberg et al 22 reported the presence of auto-antibodies to the folate receptor in 75% of mothers who had given birth to NTD-affected infants, but in only 10% of mothers of non-malformed infants. This discrepancy in frequency correlated with a greater than 25-fold increase in the risk of NTDs in the infants of mothers that carried these antibodies.…”
Section: Folic Acid Prevents Neural Tube Defectsmentioning
confidence: 99%